Un siècle de biogéographie française - Marianne Cohen; Marc Galochet; Micheline Hotyat (Bulletin de l’Association de Géographes Français)
French biogeography has undergone changes in its approaches over the course of the years, constantly renewing its questions and methods. Crossing several periods during the 20th century, the geographers’ biogeography experienced a true renaissance in the 1960s, marked by the legacy of H. Gaussen, P. Rey (cartography of vegetation and plant associations) and L. Emberger (bioclimates). In the 1970s, the field of study focused on forest landscapes, and was complemented by the concepts of ‘geosystem’ and ‘sylvosystem’. French biogeography was a pioneer in taking into account the action of human societies, as early as the 1970s, in line with H. Elhaï’s critique of the notion of climax. From the 1980s onwards, this led to a reflection on the relationship man-nature, one of the developments taking into consideration the geohistorical dimension, while Emberger’s work was extended to phyto-climatology. Meanwhile, the irruption of new data, methods and tools has profoundly renewed the analysis since the 1990s. Today, French biogeographers are in touch with environmental concerns, integrating new issues, thus tracing an original path.